Advances in understanding the genetic basis of inherited single gene skin barrier disorders: new clues to key genes that may be involved in the pathogenesis of atopic dermatitis Avanços no entendimento da base genética de doenças hereditárias monogênicas da barreira epidérmica: novas pistas para os principais genes que podem estar envolvidos na patogênese da dermatite atópica - Joey E Lai-Cheong; John A. McGrath (Anais Brasileiros de Dermatologia, 2006)
Increasing knowledge of genomic DNA sequences and genetic databases has led to the characterization of the molecular basis of several inherited skin disorders. In this review we summarize some of the major recent discoveries that have been made in defining the pathogenic mutations that cause inherited disorders of the skin barrier leading to skin scaling or increased transepidermal water loss in either rare disorders (Netherton’s syndrome or harlequin ichthyosis) or more common genodermatoses (ichthyosis vulgaris). These molecular breakthroughs have led to more accurate diagnoses, better genetic counselling and, where appropriate, the feasibility of DNA-based prenatal diagnosis, as well as the possibility of developing newer forms of treatment, including gene or protein therapy. Identifying the molecular basis of these conditions, especially ichthyosis vulgaris, has also provided dramatic new insight into the genetic abnormalities in the common disorder, atopic dermatitis. Thus research on the relatively rare single gene inherited skin disorders not only has benefits for patients and their families with these uncommon conditions but also has the potential to yield fresh and significant new information about very common skin diseases. O maior conhecimento sobre as de sequências genômicas de DNA e as bases de dados genéticas levou à caracterização da base molecular de várias doenças hereditárias de pele. Nesta revisão resumimos algumas das descobertas recentes mais importantes quanto à definição das mutações patogênicas que causam as doenças hereditárias da barreira cutânea, levando a descamação ou aumento da perda hídrica transepidérmica, seja em doenças raras, (síndrome de Netherton ou ictiose em Arlequim) ou genodermatoses mais comuns (ictiose vulgar). Estas descobertas moleculares têm conduzido a diagnósticos mais acurados, melhor aconselhamento genético e, quando apropriado, à possibilidade de diagnóstico pré-natal baseado em DNA, assim como desenvolvimento de novas formas de tratamento, incluindo terapia gênica ou proteica. A identificação da base molecular destas doenças, especialmente ictiose vulgar, também propiciou importante entendimento das anormalidades genéticas de doença comum, a dermatite atópica. Assim, as pesquisas em doenças hereditárias monogênicas de pele relativamente raras não apenas trazem benefícios para os pacientes e familiares, mas também têm o potencial de trazer informações novas e significativas sobre doenças de pele muito comuns.